Wide‐gap (Ag, Cu)(In, Ga)Se2 solar cells with different buffer materials—A path to a better heterojunction. (26th January 2020) - Keller, Jan; Sopiha, Kostiantyn V.; Stolt, Olof; Stolt, Lars; Persson, Clas; Scragg, Jonathan J.S.; Törndahl, Tobias; Edoff, Marika
Abstract: This contribution concerns the effect of the Ag content in wide‐gap Ag w Cu1‐ w In1‐ x Ga x Se2 (ACIGS) absorber films and its impact on solar cell performance. First‐principles calculations are conducted, predicting trends in absorber band gap energy ( E g ) and band structure across the entire compositional range ( w and x ). It is revealed that a detrimental negative conduction band offset (CBO) with a CdS buffer can be avoided for all possible absorber band gap values ( E g = 1.0–1.8 eV) by adjusting the Ag alloying level. This opens a new path to reduce interface recombination in wide‐gap chalcopyrite solar cells. Indeed, corresponding samples show a clear increase in open‐circuit voltage ( V OC ) if a positive CBO is created by sufficient Ag addition. A further extension of the beneficial compositional range (positive CBO at buffer/ACIGS interface) is possible when exchanging CdS with Zn1‐ y Sn y O z, because of its lower electron affinity (χ). Nevertheless, the experimental results strongly suggest that at present, residual interface recombination still limits the performance of solar cells with optimized CBO, which show an efficiency of up to 15.1% for an absorber band gap of E g = 1.45 eV. Abstract : Wide‐gap (Ag, Cu)(In, Ga)Se2 solar cells with varying absorber composition and different buffer layers were processed and characterized. As predicted by the presented first‐principles calculations, a detrimental negative conduction band offset at the interface between the CdS buffer and the absorber can be avoided by adjusting the Ag addition level to balance the Ga concentration. Interface recombination is further reduced when changing to an alternative (Zn, Sn)O buffer layer, thereby paving the way to narrow the efficiency gap between wide‐gap and low‐gap chalcopyrite solar cells.